2004
DOI: 10.1158/0008-5472.can-04-1176
|View full text |Cite
|
Sign up to set email alerts
|

Haploid Inactivation of the Amplified-in-Breast Cancer 3 Coactivator Reduces the Inhibitory Effect of Peroxisome Proliferator-Activated Receptor γ and Retinoid X Receptor on Cell Proliferation and Accelerates Polyoma Middle-T Antigen-Induced Mammary Tumorigenesis in Mice

Abstract: The amplified-in-breast cancer 3 (AIB3) is a nuclear receptor coactivator amplified and overexpressed in human breast cancers. AIB3 ؊/؊ mice die during gestation, whereas AIB3 ؉/؊ mice exhibit normal development. Here, we demonstrate that AIB3 protein is mainly located in the nuclei of mammary epithelial cells and tumor cells and its levels are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…For example, a recent study suggests that the coactivator amplified-in-breast cancer 3 is needed for the (21). Studies from our own group also indicate that responsiveness to rosiglitazone requires at least one functional PTEN allele such that tumors with homozygous PTEN deletions or promoter mutations would prove refractory to treatment (22).…”
Section: Discussionmentioning
confidence: 93%
“…For example, a recent study suggests that the coactivator amplified-in-breast cancer 3 is needed for the (21). Studies from our own group also indicate that responsiveness to rosiglitazone requires at least one functional PTEN allele such that tumors with homozygous PTEN deletions or promoter mutations would prove refractory to treatment (22).…”
Section: Discussionmentioning
confidence: 93%
“…First, in an interesting study carried out in mouse models (31), haploid inactivation of ASC-2 was found to accelerate polyoma middle-T antigen-induced mammary tumorigenesis. Second, PTIP, which has been proposed to play important roles in cellular responses to DNA damage (32,33), recently was identified as an additional component of ASCOM (9,10).…”
Section: Targeted Inactivation Of Mll3 H3k4 Methyltransferase Activitmentioning
confidence: 99%
“…The WT/PyMT and SRC-1 Ϫ/Ϫ /PyMT mammary tumor tissues (Ϸ1 mm 3 in size) were sliced from primary tumors of different donor mice and reciprocally implanted into the mammary fat pads of 8-to 12-weekold female SRC-1 Ϫ/Ϫ and WT recipient mice as described (8,35). Tumor growth was monitored once a week.…”
Section: Examination Of Lung Metastasismentioning
confidence: 99%
“…Expression of the MMTV-PyMT transgene in mice causes rapid formation of mammary carcinomas with all identifiable stages similar to human breast cancer progression (33). Extensive lung metastasis also develops in all MMTV-PyMT mice (8,(33)(34)(35), which makes the animal model ideal for investigating the role of SRC-1 in breast cancer metastasis. Furthermore, biological markers expressed in PyMT-induced mammary tumors are consistent with those expressed in human breast cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation